Numerical simulation study on inferring the location of subsurface karst water channels using shallow geothermal field data - Qing Zhang; Renzhe Zeng; Zongfang Chen; Yunfeng Li; Weiya Ge; Yuanzhi Lu; Junhao Qiu (PLoS ONE, 2025)
Karst structures significantly impact the environment and engineering projects. The presence of water-bearing karst structures alters the shallow stratigraphic temperature field. The shallow temperature measurement method offers a simple and efficient approach to obtain shallow ground temperature data, enabling the inference of karst structure distribution through temperature anomalies. In this study, the feasibility of using shallow thermometry to detect karst pipeline structures was investigated via numerical simulation at the Hongsheng Coal Coking Plant and its surrounding sites in Panzhou City, Guizhou Province, China. The results indicate that variations in the burial depth of karst structures markedly influence shallow stratum temperatures. For a single karst conduit with an equivalent diameter of 0.5 m and water temperature of 12 °C, the detectable depth limit is approximately 66 m. Although an increase in the effective flow cross-sectional area affects shallow stratigraphic temperatures, changes in equivalent diameter under the site-specific conditions alter the temperature at 2 m depth by less than 0.02 °C, making it difficult to identify the effective flow cross-sectional area using shallow thermometry. Variations in fluid temperature within a certain range (12–18 °C) also affect shallow ground temperatures, with the influence of lower-temperature fluids being more pronounced. This study provides a rapid, cost-effective, and relatively accurate method for investigating subsurface karst structures, offering important implications for related engineering applications.